The consequences of an untimely diagnosed mesiodens: Case report - Tomić Slavoljub; Janković Svjetlana; Smrekić Bojana; Đorđević Stevanka (Stomatološki glasnik Srbije, 2007)
Supernumerary teeth may have all characteristics of normal teeth (dens supernumeratus) or, more frequently, appear as rudimentary remains of the tooth bud (dens accessories). Such teeth may cause various complications and the most frequent are orthodontic anomalies and follicular cysts. Among all supernumerary teeth, the most frequent is mesiodens. It may be of different shape, but most often is conical. Untimely diagnosed and treated mesiodens may, in older age, result in complications and compromise prosthodontic rehabilitation. The aim of this study was to present a case where untimely treatment (diagnostics and extraction) of a mesiodens resulted in the formation of a follicular cyst and a partial resorption of the root of an adjacent tooth (central incisor), which had to be extracted. The patient sought a prosthodontic treatment. However, a hazelnut-size tumor was found in the upper anterior region. Clinical and X-ray examination implied the presence of a follicular cyst around a supernumerary tooth, which was situated between upper central incisors. Cystical sac was removed in a usual manner along with the extraction of the impacted mesiodens. Unfortunately, the upper central left incisor had to be extracted as well due to a progressed root resorption.